THE EFFECTIVENESS OF ELECTRONIC DICTIONARY IN LEARNING VOCABULAY AT INDONESIAN JUNIOR HIGH SCHOOL CONTEXT - Nini Sarmila; Andi Muhammad Yauri; Herman Resyadi (Institut Agama Islam Negeri (IAIN) Bone, 2022)
The main objective of this research is to find out the effectiveness electronic dictionary in learning vocabulary at Indonesian junior high school context. The method employs pre-experimental with pre-test and post-test design, 15 students is involved as the participants of the research. The result of this research reports that there is a significant increase on students’ vocabulary, proven by the value of sig. (2-tailed) is 0.00 0.05. This indicates that H1 is accepted and H0 is rejected. It is assumed that there is a significant difference between the students’ vocabulary after being giving treatment. This is evidenced by the high average students’ post-test score compared to the pre-test, which means it is effective to use electronic dictionary in learning vocabulary.